Aromaticity study of singlet‐ and triplet‐state corannulene dianion and dication. (19th September 2022) - Aleksić, Jovana; Stojanović, Milovan; Baranac‐Stojanović, Marija
Abstract: Aromaticity rules in the ground singlet state and the first excited triplet state are exactly opposite, as shown by Baird. Thus, (4n + 2)π electron annulenes are antiaromatic and 4nπ annulenes are aromatic in their triplet state. In this work, we employ quantum‐mechanical calculations at the density functional theory (DFT) level to examine (anti)aromaticity of singlet and triplet corannulene dianion and dication in their bowl‐shaped ground‐state structure and planar transition‐state structure. We find that singlet dianion contains aromatic hub and antiaromatic rim, whereas singlet dication is an antiaromatic system. This agrees with previous calculations of current density induced by perpendicular magnetic field. For triplet dianion, we find that it can be described as having aromatic rim and nonaromatic hub. Triplet dication was found to be nonaromatic, though in planar transition‐state structure, locally and semiglobally antiaromatic naphthalene subunit and aromatic central ring can be discerned. Abstract : A potential of corannulene dianion and dication to adjust their electronic structure to form doubly Hückel/Baird aromatic annulene within an annulene in their first excited triplet state was studied computationally at the density functional theory (DFT) level. Dianion was found to develop Baird aromatic rim, but nonaromatic hub, whereas dication is best described as a nonaromatic species.